ANALISIS PROYEK VIDEO MAHASISWA PGSD PADA MATA KULIAH PENDIDIKAN ANTIKORUPSI DI STKIP TAMAN SISWA BIMA - Edy Suparjan; Ahmadin Ahmadin; Rusdin Rusdin (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Based on the observations of the author of STKIP Taman Siswa Bima in the Elementary School Teacher Education study program, it is the study program that uses the most learning video media in providing material and assignments for students, more specifically in the Anti-Corruption Course the use of video as a model for student assignments has been carried out for the last three years . Where the form of assignment in the form of making an Anti-Corruption campaign video is expected to provide many opportunities for students to be creative and innovative in producing work and can provide motivation and self-expression abilities for the student in question. Learning outcomes other than limited face-to-face meetings also use the Hibrid method, namely by using the Google Classroom application and collecting assignments by uploading assignments in the form of videos on Youtube. The purpose of this study was to analyze student learning assignment videos in anti-corruption education courses. This research is a type of quantitative and qualitative descriptive research that seeks to analyze instructional videos including; the advantages and disadvantages of videos made by students. The method used is the observation of task assessment with certain criteria then data analysis displays Frequency distribution tables, Graphs, Means and standard deviation. The focus of the analysis is to look for errors in duration, originality of the recording, suitability with the presentation material, sound and image quality. The rating criteria scale used is 50-100. The results of the study found that the average score for student videos was 76. In terms of criteria, the lowest score was the quality of the material concept, which was 72. Meanwhile, the highest score was the duration and originality of the video, which were 79-80 respectively.